Potential of natural technologies for decentralised wastewater management in India - Starkl, M.; Amerasinghe, Priyanie H.; Essl, L.; Jampani, Mahesh; Kumar, D.; Asolekar, Shyam R. (2012)
High population growth, increasing urbanization and rapid economic development are exerting pressure on the already scarce water resources in India. Untreated wastewater from human settlements reaching natural waterways is very common contributing to environmental pollution, which directly affects the availability of fresh water for human consumption. Therefore, treatment and reuse of wastewater can play an important role in addressing some of the urban water challenges in India. Conventional treatment plants have many challenges, therefore, natural treatment systems are viewed as a cost-effective alternative, which are more suitable in the Indian context. For example, they are not reliant on electricity, easier to maintain, can be part of small decentralised systems and work well in tropical climates. This study presents a rapid sustainability assessment and a review of the potential of natural treatment systems in India. The preliminary results show that the natural treatment systems have a high potential for wastewater treatment. However, there are still gaps in knowledge related to aspects that hinder the sustainable functioning of these treatment systems.